Performance evaluation in Public Administration: P-AHP and PROMETHEE a comparative analysis - Gerarda Fattoruso; Antonio Violi; Stefania Pizzimenti; Sonia Suraci; Marco Vesperi (Ratio Mathematica)
The performance evaluation is a crucial phase for each organization, and nowadays this is particularly relevant also for Public Administrations (PAs), where a high level of efficiency and effectiveness has a meaningful impact on citizens and companies. In this work we propose the adoption of Multi Criteria Decision Making approaches, in particular PROMETHEE I-II and Parsimonious AHP, for the performance evaluation of PA's services. The methods have been tested on a real PA in Southern Italy, and the results show their effectiveness as control and planning support tools.